2017
DOI: 10.3347/kjp.2017.55.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characteristics and Phylogenetic Trends of Trematode Cercariae in Freshwater Snails from Nakhon Nayok Province, Thailand

Abstract: The prevalence of cercarial infection in freshwater snails and their evolutionary trends were studied in Nakhon Nayok province, Thailand. A total of 2,869 individual snails were examined for parasitic infections. The results showed that 12 snail species were found to host larval stages of trematodes with an overall prevalence of 4.7%. The infected specimens included 7 types at the cercarial stage; cercariae, megalurous cercariae, echinostome cercariae, furcocercous cercariae, parapleurolophocercous cercariae, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…helena , L. auricularia, and Co. javanica were found not to be infected with any cercariae in this study, however this is in contrast to other studies. For example, it was found that L. auricularia was the most important intermediate snail host for transmitting a wide variety of trematodes in Thailand [ 51 , 52 ]. Many records in Thailand pointed to Bithynia snails being the key link in the liver fluke, Opisthorchis viverrini .…”
Section: Discussionmentioning
confidence: 99%
“…helena , L. auricularia, and Co. javanica were found not to be infected with any cercariae in this study, however this is in contrast to other studies. For example, it was found that L. auricularia was the most important intermediate snail host for transmitting a wide variety of trematodes in Thailand [ 51 , 52 ]. Many records in Thailand pointed to Bithynia snails being the key link in the liver fluke, Opisthorchis viverrini .…”
Section: Discussionmentioning
confidence: 99%
“…Trematodes are internal parasites with a complex life cycle which includes a number of stages with parthenogenetic and amphimictic (mostly hermaphroditic) generations, as well as alternating hosts, invertebrates and vertebrates (Blasco-Costa, Poulin, 2017;Zhytova, Kornyushin, 2017). Th e fi rst intermediate host in that life cycle is almost always a molluscs (Serbina, 2014;Zhytova, Zhytov, 2016;Faltynkova, 2016;Gordy et al, 2016;Chontananarth, 2017), in which parthenogenetic generations of trematodes develop. Th e second intermediate host can be animals of diff erent systematic groups, mainly invertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…In Thailand, the studies related to snails diversity and cercarial infection are insufficient (911), especially in Sirindhorn Reservoir where is an important area used for agricultural purposes, animal husbandry, also the source of fish farming. No study has been surveyed snail diversity and parasitic infection in snail in Sirindhorn Reservoir, Ubon Ratchathani Province, Thailand.…”
Section: Introductionmentioning
confidence: 99%